Patient Understanding of Medication Adherence in Hypertension within Medical Surgical Care - Susyanti, Eny; Annisa, Mutia; Juwarni, Sri (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores patients’ understanding of medication adherence in managing hypertension within a medical-surgical care setting. Using a phenomenological qualitative approach, semi-structured interviews were conducted with 12 hospitalized hypertension patients in a type B general hospital in Jakarta. Thematic analysis revealed three key themes: limited understanding of the long-term benefits of antihypertensive therapy, perceived barriers related to complex treatment regimens and hospitalization conditions, and the crucial role of healthcare communication in encouraging adherence. The study concludes that cognitive, emotional, and relational factors strongly influence patients’ adherence behaviors. Strengthening health education, optimizing nurse–patient communication, and implementing individualized interventions are recommended to improve hypertension management and support patient-centered care in medical-surgical environments.